النظام القانوني الجزائري لحماية حق براءة الاختراع - بلجبل, عتيقة (جامعة الوادي University of Eloued, 2017)
تعد براءة الاختراع حقا من حقوق الملكية الفكرية؛ حيث يضمن لها هذا الحق الحماية القانونية، فبراءة الاختراع أداة لتنفيذ سياسة التطور الاقتصادي والتكنولوجي باعتباره وسيلة لتشجيع الابتكارات المحلية ؛إذ يعترف القانون للمخترع بحق خاص على ابتكاره والاستفادة منه ماليا، فيلتزم كل مالك للاختراع بالكشف عن المعلومات المتعلقة باختراعهم للجمهور من أجل إثراء المعارف التقنية مقابل الحماية بموجب البراءة الممنوحة له، ونتيجة لما تقتضيه مبادئ العدالة والمصلحة العامة للمجتمع لا يكون للمخترع حق دائم مؤبد على ابتكاره بل لابد من تقييده لمدة محددة قانونا وخلال هذه المدة يمنع على الغير استعمال أو استغلال المخترع موضوع الحماية وإلا كان عرضة للجزاءات المقررة قانونا. Abstract: The patent is considered as a right from intellectual property rights these last insure a legal protection to the patent . So the patent is a tool to implement the economical and technological development’s policy which is considers as a way to encourage local innovations , So; the law recognizes a private ( special ) right and financial benefit to the creator on his invention . Every creator must reveal the informations relating to his invention to the public for enriching the technical knowledges versus the protection under the patent given to him . The result as required by the principles of justice and the public interest community the inventor does not have a permanent right on his invention , but this right must be restrained by law for a limited period and during this period it prevents others use or exploitation of the invention which is protected , they will be punished by law .
Keywords: براءة اختراع؛ حقوق الملكية الفكرية؛ الابتكار